Gamification for online training of court professionalsin a Labour Court in São Paulo, Brazil (TRT-2): what can be implemented in Moodle 2.5 - Ludmilla Cavarzere de Oliveira; Valquíria Trovão Cavalli; Álvaro Machado Dias; Mauri Aparecido de Oliveira (Universidade Nove de Julho, 2018)
This paper is part of a master's thesis which dealt with implementation of gamification in an online course offered by Judicial School at São Paulo Regional Labour Court. The question of this paper is to review relevant literature about benefits and pitfalls of gamification in learning contexts to propose a framework for implementing gamification in Moodle 2.5. The objective of this paper is to compare the creation of a framework of an online course without game elements with its gamified version with elements that can motivate and engage people in online learning contexts, such as activity completion, restricted access, progress bar block, badges, and jeopardy-like quizzes. After implementing these features in an existing online course without gamification, the main results are that it is feasible to implement simple game mechanics in Moodle 2.5, although it takes a long time to create some of them, such as badges, and it is mandatory to have knowledge of development if the course demands Moodle documentation to create a more complex gamification block.